Infundibular tanycytes as modulators of neuroendocrine function: hypothetical role in the regulation of the thyroid and gonadal axis - Lechan, Ronald M.; Fekete, Csaba (Acta Biomedica Atenei Parmensis, 2007)
Tanycytes comprise a heterogeneous population of specialized cells of glial origin that line the floor and ventrolateral walls of the third ventricle between the rostral and caudal limits of the hypothalamic median eminence. While morphologic and ultrastructural features suggest a role as barrier cells, creating separate compartments between the cerebrospinal fluid, median eminence and hypothalamus, tanycytes likely have multiple other important functions that have yet to be fully elucidated. Possibilities to consider are a role in neuroendocrine regulation including modulation of the hypothalamic-pituitary-thyroid axis during fasting and infection, regulation of reproductive function, particularly in seasonal breeders, and in feeding.